Acquisition of Behavioral Skills after Manikin-Based Simulation of Neonatal Resuscitation by Fellows in Neonatology - Guerreiro, Maiana D. M.; Ogata, Joice F. M.; Sanudo, Adriana; Prestes, Ana Claudia Y.; Conzi, Maria F.; Kawakami, Mandira D.; Miyoshi, Milton H.; Almeida, Maria Fernanda B. de; Guinsburg, Ruth (American Journal of Perinatology, 2022)
Objective Behavioral performance of health professionals is essential for adequate patient care. This study aimed to assess the behavioral skills of fellows in neonatology before and after a simulation training program on neonatal resuscitation.Study Design From March 2019 to February 2020, a prospective cohort with 12 second-year fellows in neonatology were evaluated during three training cycles (16 hours each) in manikin-based simulation of neonatal resuscitation with standardized scenarios. Each cycle lasted 1 month, followed by a 3-month interval. One video-recorded scenario of approximately 10 minutes was performed for each fellow at the beginning and at the end of each training cycle. Therefore, each fellow was recorded six times, before and after each one of three training cycles. Anxiety of the fellows was assessed by the Beck Anxiety Inventory applied before the first training cycle. The videos were independently analyzed in a random order by three trained facilitators using the Behavioral Assessment Tool. The behavioral performance was evaluated by repeated measures of analysis of variance adjusted for anxiety and for previous experience in neonatal resuscitation.Results Fellows' overall behavioral performance improved comparing the moment before the first training and after the second training. The specific skills, such as communication with the team, delegation of tasks, allocation of attention, use of information, use of resources, and professional posture, showed a significant improvement after the second month of training. No further gains were noted with the third training cycle. Anxiety was observed in 42% of the fellows and its presence worsened their behavioral performance.Conclusion An improvement in behavioral performance was observed, comparing the moment before the first training and after the second training, without further gains after the third training. It is worth noting the important role of anxiety as a modulator of acquisition and retention of behavioral skills in health professionals in training.Key Points
Keywords: cardiopulmonary resuscitation; newborn; simulation training; behavioral rating scale; anxiety; internship and residency; behavior